Bionics in Engineering Education Considerations, Experiences and Conclusions - Ralf Neurohr; Cristian Dragomirescu (Applied Bionics and Biomechanics)
During recent years bionics, a new discipline which is in charge with the transfer of the principles of construction, regulation, interaction and organisation of biology into innovative technical solutions, has attracted significant interest from various industries. Based on this request for bionic expertise in engineering, the faculty for teaching engineering in foreign languages (FILS) at ‘Politehnica’ University of Bucharest started a course in bionics in SS 2007, which was supported by the expertise of the German ‘Bionik-Kompetenz-Netz’, one of the leading organizations in bionics. This is the report on the considerations involved in the course concept, the first experiences with the students' acceptance, some conclusions and future perspectives for extending bionics activities at ‘Politehnica’. Finally, within the last section, the evaluation of a questionnaire, filled in by the students at the end of the course, will be presented. In order to avoid any confusion, considering overlapping or mixing up with other bio-disciplines related to technology, the paper starts with a short introduction, explaining the principles of bionics and providing a clear definition of the field.